MENSTRUAL DISORDER AND QUALITY OF LIFE AMONG FEMALE COLLEGE ADOLESCENTS IN SELANGOR - Faieza Samat; Nurul Atiqah Mohamad Azam G; Amalina Alya Azizan; Nur Azurah Abdul Ghani (Asian Journal of Medicine & Health Sciences, 2020)
Background: Menstrual disorder is a womanhood problem around the world and negatively affects the quality of life. In females, common menstrual disorders are dysmenorrhoea, oligomenorrhoea and menorrhagia. Methodology: A cross-sectional study was carried out among 294 female college adolescents aged 18 to 20 years in UKM, UM and UiTM. A set of questionnaires on demography, menstrual patterns and health-related quality of life was distributed online over a period of about 10 days in December 2019. Results: A total of 294 questionnaires were analysed. The mean age of the participants was 18.36±0.64 years with a range of 18 to 20 years. Of all participants, 53% had dysmenorrhoea ranging from moderate to very severe while 16% had menorrhagia while 10% had oligomenorrhoea. Quality of life in females with menstrual disorders were poor (43.56 ± 6.31) compared to the normal females (46.67 ± 5.58) in physical and mental health with p-value